2017
DOI: 10.1108/ijmf-01-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

The real effects of primary and secondary equity markets on firm performance

Abstract: Purpose The purpose of this paper is to investigate the real effects of primary and secondary equity markets on the post-issue operating performance of initial public offering (IPO) firms. Design/methodology/approach The author utilizes the intended use of proceeds as a proxy variable for the primary market and the investment-to-price sensitivity and the informativeness of stock prices as alternative proxy variables for the secondary market. The compositional data, and non-parametric quantile regressions whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…In contrast, using the De Bondt and Thaler’s (1985) approach, Pasaribu (2011) found no symptom of overreaction anomaly at three-month, six-month and annual periods of the LQ-45 stocks in Indonesia during the 2003-2007 period. Similar to Sumiyana (2009); Faisal and Majid (2016) and Andriansyah (2017) document market anomaly in the big-open Indonesian emerging market. The former study found the existence of the calendar effects of the turn-of-month and the weekend effects during the period 2001-2014, while the latter study found that the operating performance of the firms was positively and negatively influenced by investment-to-price sensitivity and information pricing errors, respectively.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…In contrast, using the De Bondt and Thaler’s (1985) approach, Pasaribu (2011) found no symptom of overreaction anomaly at three-month, six-month and annual periods of the LQ-45 stocks in Indonesia during the 2003-2007 period. Similar to Sumiyana (2009); Faisal and Majid (2016) and Andriansyah (2017) document market anomaly in the big-open Indonesian emerging market. The former study found the existence of the calendar effects of the turn-of-month and the weekend effects during the period 2001-2014, while the latter study found that the operating performance of the firms was positively and negatively influenced by investment-to-price sensitivity and information pricing errors, respectively.…”
Section: Introductionsupporting
confidence: 61%
“…The study found that noise and overreaction phenomena were commonly occurring in the opening and closing prices, and the investors simultaneously corrected the noise and overreaction during the first 30-min interval on every trading day. Andriansyah (2017) investigates the real effects of primary and secondary equity markets on the post-issue operating performance of initial public offering firms in the Indonesian stock market over the period 1999-2013. The study found that the firm operating performance was related to the firm’s motivation to go public.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations